The association between the serum fat-soluble vitamins (A, D and E) and the intake of live microbes: a national population based cross-sectional study - Zheng, Huiling; Liu, Chan; Xu, Dan; Li, Mei; Hong, Hua (Frontiers in Nutrition, 2025)
ObjectiveFat-soluble vitamins (FSVs) play essential roles in numerous physiological processes and are involved in the onset and progression of chronic diseases. However, limited research has investigated whether dietary intake of live microbes correlates with circulating FSVs levels. This study aims to explore the relationship between the dietary intake of live microbes and the serum levels of FSVs.MethodsWe conducted a cross-sectional analysis on a nationally representative sample of 27,668 participants from the National Health and Nutrition Examination Survey (NHANES) to assess the association between serum levels of FSVs and the intake of dietary live microbes. Weighted generalized linear regression and logistic regression models were used to evaluate the associations, adjusting for demographic, lifestyle, laboratory, and dietary covariates.ResultsAfter multivariate adjustment, each one-unit increase in the natural log-transformed MedHi food intake corresponds to an increase of 0.17 μg/dL in vitamin A (95% CI: 0.04, 0.30), 0.36 nmol/L in vitamin D (95% CI: 0.22, 0.51), and 4.65 μg/dL in vitamin E (95% CI: 1.91, 7.39). Furthermore, the exposure-response curves for MedHi consumption showed a consistent decreasing trend in the prevalence of low serum levels of these FSVs.ConclusionIn conclusion, this study provides evidence that the dietary intake of live microbes is associated with increased serum levels of FSVs and may contribute to reducing deficiencies in these vitamins.